2017
DOI: 10.1200/jco.2015.66.2510
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase II Study of Azacitidine Alone or in Combination With Lenalidomide or With Vorinostat in Higher-Risk Myelodysplastic Syndromes and Chronic Myelomonocytic Leukemia: North American Intergroup Study SWOG S1117

Abstract: Purpose Azacitidine is standard, first-line therapy in higher-risk myelodysplastic syndromes (MDS). Whether azacitidine-based combinations with lenalidomide or vorinostat produce superior overall response rates (ORRs) to azacitidine is not known. Patients and Methods North American Intergroup Study S1117 is a phase II/III trial that randomly assigned patients with higher-risk MDS and chronic myelomonocytic leukemia (CMML) 1:1:1 to azacitidine (75 mg/m/day on days 1 to 7 of a 28-day cycle); azacitidine plus len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
162
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 216 publications
(172 citation statements)
references
References 32 publications
9
162
1
Order By: Relevance
“…This observation is consistent with previous randomized studies in high-risk MDS but is the first demonstration that HDAC inhibitors have no impact on clinical outcomes in patients with newly diagnosed or relapsed AMLtreated with AZA (10)(11)(12). Why might our study have failed to replicate earlier single arm studies of strikingly increased clinical activity of combined AZA and HDAC inhibitor treatment (8,9,22)?…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This observation is consistent with previous randomized studies in high-risk MDS but is the first demonstration that HDAC inhibitors have no impact on clinical outcomes in patients with newly diagnosed or relapsed AMLtreated with AZA (10)(11)(12). Why might our study have failed to replicate earlier single arm studies of strikingly increased clinical activity of combined AZA and HDAC inhibitor treatment (8,9,22)?…”
Section: Discussionsupporting
confidence: 91%
“…Although recent randomized trials have reported no benefit of combined AZA and HDAC inhibitor therapy in patients with high-risk MDS, there have been no randomized trials in AML (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, all of them have failed to improve response rate and survival when compared to monotherapy with HMA [69]. Nevertheless, based on early positive signal from one of these trials [70] some combinations are currently also under investigation for treatment of relapse after allo-SCT.…”
Section: Potential Combination Partnersmentioning
confidence: 99%
“…This has prompted combination therapy with HMA and immunomodulatory agents due to postulated synergistic effects [72]. A randomized phase II intergroup study (S1117) evaluated AZA + lenalidomide, AZA + vorinostat (HDACi), versus AZA monotherapy in MDS and CMML [73]. The median follow-up was 9 months, and no statistically significant difference was seen in response rates across all three arms.…”
Section: Epigenetic Modifying Agentsmentioning
confidence: 99%